Implementation of a novel efficacy score to compare sealing and cutting devices in a porcine model - Brecht, Lea; Wallwiener, Markus; Schott, Sarah; Domschke, Christoph; Dinkic, Christine; Golatta, Michael; Schütz, Florian; Fluhr, Herbert; Stenzinger, Albrecht; Kirchner, Marietta; Sohn, Christof; Rom, Joachim (Surgical endoscopy and other interventional techniques, 2018)
Background: In general surgery, minimally invasive laparoscopic procedures have been steadily increasing over the last decade. The application of advanced bipolar and ultrasonic energy devices for sealing and cutting of blood vessels plays a vital role in routine clinical procedures. The advantages of energy-based instruments are enhanced sealing capability combined with both fast sealing time and minimal thermal injury. The purpose of this study was to compare the safety and efficacy profiles of nine laparoscopic sealing and cutting devices in a porcine model, with a new scoring system. Methods: Comparative studies in a porcine model were performed to assess vessel sealing, burst pressure, thermal spread, maximum heat, sealing/cooling time, and compression strength over the full jaw. Nine different devices from five manufacturers were tested in this study. The sealing and cutting devices (SCD) score has been developed to enable standardized comparisons of various devices. For this purpose, the most important parameters were identified through a consensus approach. Results: All sealed vessels with different devices could withstand a median pressure of more than 300 mmHg (range 112-2046 mmHg). The time for the sealing procedure was 7.705 s (range 5.305-18.38 s) for the ultrasonic and 7.860 s (range 5.08-10.17 s) for the bipolar devices. The ultrasonic instruments reached a median temperature of 218.1 °C (range 81.3-349.75 °C) and the bipolar devices a temperature of 125.5 °C (range 94.1-133.35 °C). The tissue reached a median temperature of 61.9 (range 47.1-80.6 °C) after ultrasonic sealing and 76.7 °C (range 63.1-94.2 °C) after bipolar sealing. The median SCD score was 10.47 (range 7.16-13.72).ConclusionAll the instruments used seemed safe for use on the patient. The SCD score allows an indirect comparability of the instruments.